A comparative analysis of assurance fund vis-à-vis title insurance: which offers better compensation for victims of land disputes in Malaysia?. (4th May 2021) - Halid, Shahrul Natasha; Hassim, Jady @ Zaidi
ABSTRACT: Land transactions are fraught with risk because of the nuances of property law and conveyancing practices, as well as skyrocketing land prices. This is demonstrated by the frequent occurrences of land title disputes which often leads to unsatisfactory litigation consequences for landowners. However, some landowners may be able to seek compensation through title insurance or assurance funds. This article explores the differences between assurance funds and title insurance by analysing the benefits and weaknesses of both as implemented in various jurisdictions. This research is critical for developing countries, such as Malaysia which is currently considering implementing a practical and effective scheme, to serve as a buffer against land-related litigation.